STATE OF THE ART IN CALCITE AND POLYOLEFINS RECYCLING - Croitoru, Catalin; Giubega, Adela; Patachia, Silvia; Baltes, Liana; Pascu, Alexandru; Roata, Ionut Claudiu; Tierean, Mircea (Bulletin of the Transilvania University of Brasov Series I: Engineering Sciences, 2016)
The article outlines several aspects regarding the efficientrecycling of polyolefin wastes and crystalline calcium carbonate-basedsecond raw materials (calcite) in order to obtain composite materialswith improved properties. Several bottlenecks regarding the compatibilityof the polymer with the inorganic filler are addressed, with detailing theup-to-date available solutions, as well as several other issues, related tocalcium carbonate particles aggregation and abrasivity diminishing inorder to obtain composites with improved mechanical properties andstability. The need for new ecologic and chemically stablecompatibilising agents defines the research in this domain still an openand permanently improving issue
Keywords: polyolefins; calcite; polymer wastes; recycling